Trilobatin ameliorates insulin resistance through IRS-AKT-GLUT4 signaling pathway in C2C12 myotubes and ob/ob mice - Min Liu; Lujing Wang; Xigan Li; Yucui Wu; Fei Yin; Jianhui Liu (BMC, 2020)
Abstract Background Trilobatin, a natural compound, has been found to exhibit anti-diabetic properties in high-fat diet (HFD) and streptozotocin (STZ) induced type 2 diabetic mice. But up to now no research has been reported on the effect of trilobatin on insulin resistance in peripheral tissues. Herein, we determined the effects of trilobatin on insulin resistance in palmitate-treated C2C12 myotubes and ob/ob mice. Methods Male ob/ob mice (8-10 weeks) and same background C57BL/6 mice were used to evaluate the role of trilobatin on insulin resistance; protein expression and phosphorylation were measured by western blot; glucose uptake was determined a fluorescent test. Results Treatment with trilobatin prevented palmitate-induced insulin resistance by enhancing glucose uptake and the phosphorylation of insulin resistance substrate 1 (IRS1) and protein Kinase B, (PKB/AKT), recovered the translocation of GLUT4 from cytoplasm to membrane, but preincubation with LY294002, an inhibitor of PI3K, blocked the effects of trilobatin on glucose uptake and the distribution of GLUT4 in C2C12 myotubes. Furthermore, administration with trilobatin for 4 weeks significantly improved insulin resistance by decreasing fasting blood glucose and insulin in serum, enhancing the phosphorylation of IRS1 and AKT, and recovering the expression and translocation of GLUT4 in ob/ob mice. Conclusions IRS-AKT-GLUT4 signaling pathway might be involved in trilobatin ameliorating insulin resistance in skeletal muscle of obese animal models.